La gestión empresarial y su incidencia en la rentabilidad de la empresa euro créditos del cantón La Maná, provincia de Cotopaxi, año 2012 - Salguero Vivanco, Angel Raúl (2015)
In the present research was presented as a problem of study to implement a good business management and its impact on the profit of the “EURO CRÉDITOS” company in La Maná Canton. For the theoretical foundations were consulted and analyzed a selected group of concepts and categories that explain how make a good business management through a proper resource planning in order to obtain an optimization of these, and thus to obtain profit. The methodology of this research is not experimental as it is not new, the local companies realize management in an inadequate manner because they do not know about the topic.